2021
DOI: 10.1101/2021.12.01.470669
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell transcriptome reveals insights into the development and function of the zebrafish ovary

Abstract: Zebrafish are an established research organism that has made many contributions to our understanding of vertebrate tissue and organ development, yet there are still significant gaps in our understanding of the genes that regulate gonad development, sex, and reproduction. Unlike the development of many organs, such as the brain and heart that form during the first few days of development, zebrafish gonads do not begin to form until the larval stage (≥5 dpf). Thus, forward genetic screens have identified very fe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 128 publications
(208 reference statements)
1
27
0
Order By: Relevance
“…As discussed above, inhbaa may be the major form of β subunits that contribute to the biosynthesis of inhibin in zebrafish. The single cell transcriptome data showing coexistence of inha and inhbaa , but not inhbab and inhbb , in the granulosa cells further support this idea [84].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As discussed above, inhbaa may be the major form of β subunits that contribute to the biosynthesis of inhibin in zebrafish. The single cell transcriptome data showing coexistence of inha and inhbaa , but not inhbab and inhbb , in the granulosa cells further support this idea [84].…”
Section: Discussionmentioning
confidence: 93%
“…By comparison, inhbb was mostly expressed in the stromal and germ cells (oocytes) with weak signals in the granulosa and theca cells. Interestingly, the expression of inha was exclusively localized in the granulosa cells, coexisting mostly with that of inhbaa [84]. These data suggest that in zebrafish ovary, at least in newly-formed young follicles at 40 dpf, different forms of activin molecules (activin A, B and AB) can be formed in all types of cells including granulosa, theca and stromal cells as well as the oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…4G). We noted that recently published bulk RNA-seq data from the hydrozoan Hydractinia symbiolongicarpus showed that ebf was specifically expressed in polyps undergoing oogenesis (DuBuc et al 2020) and that an ebf ortholog, ebf3b , is a marker of female germline stem cells in zebrafish (Liu et al 2021). Therefore, ebf regulation of oogenesis may predate the split of Bilateria and Cnidaria.…”
Section: Resultsmentioning
confidence: 99%
“…If the turquoise killifish piRNA metabolism dynamics are similar to those of zebrafish, the depletion of PIWI at middle-age could merely indicate a higher proportion of mature oocytes (Liu et al, 2022). Alternatively, increased TE expression in middle-aged ovaries (and thus decreased TE control) may be a symptom of decreased oocyte quality before fertility starts to decline, suggesting that reproductive aging may precede organismal decline.…”
Section: Dynamic Te Control In the Aging African Turquoise Killifish ...mentioning
confidence: 99%
“…To note, as seen in Supplementary Table S1C, genes belonging to the "piRNA metabolic process" GO terms are, as expected, robustly expressed in killifish gonads throughout life. Intriguingly, in zebrafish, the gene encoding PIWIL1, the primary catalytic protein of the PIWI pathway, is expressed most highly in developing germline stem cells before expression decreases in more mature oocytes (Liu et al, 2022), which could indicate a higher ratio of mature oocytes to developing germline stem cells in middle-aged killifish ovaries compared to young and old ovaries. Thus, downregulation of PIWI-related genes at mid-age may be related to differences in mature oocytes content.…”
Section: Aging Differentially Impacts Gene Expression In Turquoise Ki...mentioning
confidence: 99%